2021
DOI: 10.1177/22808000211058867
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Comparison of adhesive bond strength among fiber reinforced post and core with different cementation techniques: In vitro study

Abstract: Aim: To investigate push-out bond strength (PBS) of fiber post to radicular dentin after using different cementation techniques. Material and methods: Sixty single-rooted premolars were disinfected and cleaned by mechanical instrumentation. S1, S2, and SX were used for canal shaping and finishing of the canal was carried out using F1 and F2. This was followed by constant irrigation and smear layer removal using 17%EDTA. The canal was dried filled with gutta-percha and canal space was prepared using a peso ream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Although a variety of materials and protocols for post cementation have been extensively analyzed, in vitro investigations have provided contradictory findings. Several studies have shown significantly higher bond strength values (Table 1) for self-adhesive luting cement [37][38][39][41][42][43][44][45]51,52], while others have shown comparable behaviors among the adhesive systems available [22,46]. In fact, it has been reported that the composition of the self-adhesive resin cement favors a positive performance, due to a greater moisture tolerance than self-etching cement for instance [38,42].…”
Section: Cementationmentioning
confidence: 99%
“…Although a variety of materials and protocols for post cementation have been extensively analyzed, in vitro investigations have provided contradictory findings. Several studies have shown significantly higher bond strength values (Table 1) for self-adhesive luting cement [37][38][39][41][42][43][44][45]51,52], while others have shown comparable behaviors among the adhesive systems available [22,46]. In fact, it has been reported that the composition of the self-adhesive resin cement favors a positive performance, due to a greater moisture tolerance than self-etching cement for instance [38,42].…”
Section: Cementationmentioning
confidence: 99%
“…However, glass fiber posts adhesively cemented into root canals, with a modulus of elasticity similar to the dentin, provide greater flexibility to endodontically treated teeth when subjected to occlusal forces and improve the homogeneous distribution of stress at the post-cement-dentin interface and along the radicular surface [9][10][11][12][13][14][15]. The adhesive procedure of luting the fiber posts into root canals using resin-based cements with similar mechanical properties makes the entire complex behave as a homogeneous entity during functions, preventing fracture [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a clinician must be able to choose the most adequate restorative approach to restore endodontically treated teeth (ETT), as these latter become more vulnerable to fracture than vital teeth [4]. Indeed, during endodontic treatments, a great amount of dental tissue may be removed, especially due to the preparation and disinfection steps; this may represent the key cause for the tooth structure to become weak [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, some of these materials, such as metal or ceramic, may increase the risk of fracture in the remaining tooth structure due to their high modulus of elasticity, and they may produce gray discoloration of the crown [18]. Conversely, fiberglass postand-core systems present a modulus of elasticity similar to that of dentin, which may provide favorable results in terms of biomechanical and aesthetic properties [5,23]. PaC systems can be manufactured in different angulations, sizes, and shapes with high precision and efficiency using CAD/CAM technology [23].…”
Section: Introductionmentioning
confidence: 99%